SIKUEN STRATIGRAFI DAN PALEOGEOGRAFI FORMASI TALANG AKAR PADA AREA “FERCANZA”, CEKUNGAN JAWA BARAT UTARA - Fercanza, Frisdio; Gani, Reza Muhammad Ganjar; Abdurrokhim, Abdurrokhim; Muljana, Budi; Budiana, Rahmat (Bulletin of Scientific Contribution, 2017)
ABSTRACT“FERCANZA'' area is the working area of Pertamina Hulu Energi located in North West Java Basin. This study focused on Talang Akar formation at Arjuna sub basin. This research applies the Sequence stratigraphy  concept with correlation method, which will give results in form of (1) Determination of sequences marker is more accurate, (2) Facies mapping, and (3)Sequence stratigraphy model with  higher resolution detail for determination of plays, in this case stratigraphic traps on Talang Akar Formation at "FERCANZA" area. Data used in this study include the integration of 7 well logs data, 3 side wall cores, 5 mudlog, 8 seismic line, and 1 biostratigraphy report. Sequence Boundary (SB), Maximum Flooding Surface (MFS), and other Sequence stratigraphy marker determined from well log data analysis to make a cross-correlation. Interpretation of depositional environment based on the analysis of lithofacies, elektrofacies, and seismicfacies. Based on the research results, the Formation Talang Akar on the ''FERCANZA'' area has five facies association is delta plain, delta front, pro delta, tidal channel, and shallow marine with common facies associations form of  sediment tide dominated delta and sediment shallow marine. Directions sediment supply is derived from the relative direction northwest -southeast shown by the discovery of progradation patterns to southeast of the seismic profiles were trending northwest to the southeast. Through sequences marker which have been determined, the model for deposition of Talang Akar formation is divided into 4 representation depositional models at each sequence stratigraphys marker. Representation of the model shows the conditions and morphological changes in the research areas from every phase of its.Keywords: North West Java Basin, Talang Akar Formation, Sequence stratigraphy, Depositional models ABSTRAKArea ‘’FERCANZA’’ merupakan wilayah kerja dari Pertamina Hulu Energi yang berada pada Cekungan Jawa Barat Utara. Penelitian  ini difokuskan pada Formasi Talang Akar pada sub cekungan Arjuna. Penelitian ini menerapkan konsep sequence stratigraphy dengan metode korelasi, yang akan  memberikan hasil berupa (1) Penentuan marker sikuen yang lebih akurat, (2) Pemetaan fasies, dan (3) Model sequence stratigraphydengan resolusi yang lebih detail untuk penentuan plays, dalam hal ini perangkap stratigrafi pada Formasi Talang Akar, Area “FERCANZA”. Data yang digunakan dalam penelitian meliputi integrasi dari 7 data well log, 3 side wall core, 5 data mudlog, 8 line seismik, dan 1 data biostratigrafi . Batas sikuen (SB), maximum flooding surface (MFS), dan marker sequence stratigraphylainnya ditentukan dari analisis data well log untuk membuat penampang korelasi. Interpretasi lingkungan pengendapan didasari oleh analisis lithofacies, elektrofacies, dan seismik facies. Berdasarkan hasil penelitian, pada formasi Talang Akar di Area ‘’FERCANZA’’ diketahui Formasi Talang Akar memiliki lima asosiasi fasies yaitu delta plain, delta front, pro delta, tidal channel, dan shallow marine dengan asosiasi facies umum berupa endapan tide dominated delta dan endapan shallow marine. Arah suplai sedimen berasal dari arah relatif barat laut -tenggara yang ditunjukan oleh ditemukannya pola progradasi ke arah tenggara dari profil seismik yang berarah barat laut menuju tenggara. Melalui marker sikuen yang telah ditentukan, model pengendapan untuk formasi Talang Akar dibagi menjadi 4 gambaran model pengendapan disetiap marker sequence stratigraphystratigrafi. Gambaran model tersebut menunjukkan kondisi dan perubahan morfologi daerah penelitian dari setiap fasenya.Kata Kunci : Cekungan Jawa Barat Utara, Formasi Talang Akar, Sequence Stratigraphy, Model Pengendapan